PENERAPAN MODEL PEMBELAJARAN NOVICK UNTUK MENINGKATKAN PEMECAHAN MASALAH MATEMATIS SISWA - Siregar, Yulia Anita; Lubis, Seri Wahyuni (Mahesa Research Center, 2020)
The problem in this research is the low ability of students 'problem solving, the low activity of students' mathematics learning, and the low ability of the teacher in managing learning. To overcome these problems, a Novick learning model is applied. This type of research is classroom action research. Where the population of this study was all class 11 IPA-1, totaling 31 students. Data collection techniques in this study were tests and observations. The results of the study can be seen from the test of students' problem-solving abilities in cycle I and cycle II there is an increase of 23.42% and have met the completeness criteria of â‰¥ 80% with the category